تأثير نسبة الاشابة بـ Zn(CH3COO)2,2H2O على الخصائص العزلية والكهربائية لأغشية PVA - ختام قنجراوي (Tishreen University, 2018)
A solution of PVA (Poly Vinyl Alcohol) was doped with Hydro-Zinc Acetate (Zn(CH3COO)2,2H2O) with a weight percentage of (0,10,15)% at laboratory temperature and Standard Pressure with Casting Method, using an LCR device with a frequency range of .The capacitance C and the loss factor D were measured, the rest of the electrical values such as the complex dielectric constant (Which consists of a real part  and an imaginary part ), and alternating electrical conductivity  were calculated. The study has demonstrated that increasing the Hydro-Zinc Acetate doping percentage  had noticeably affected the electrical values (C,D, , , ,etc..) improving the dielectric Properties of PVA Polymers, Increasing the values of (C,Q, , , )  while decreasing the values of (D, ). تمت اشابة محلول من بولي فينيل الكحول PVA(Poly Vinyl Alcohol) بخلات الزنك المائية Zn(CH3COO)2,2H2O (Hydro-Zinc Acetate) بالنسب الوزنية(0,10,15)%wtفي درجة حرارة المختبر والضغط الجوي النظامي بطريقة الصب (Casting Method). وباستخدام جهاز LCR على المجال الترددي  تم قياس سعة المكثفة C(Capacitance)ومعامل الفقد D(Loss Factor), ومن ثم تم حساب بقية المقادير الكهربائية كثابت العزل الكهربائي العقدي (Complex Dielectric Constant) بجزأيه الحقيقي (Real Part), والتخيلي (Imaginary Part), والناقلية الكهربائية المتناوبة (AC Electrical Conductivity). بينت الدراسة أن زيادة نسب الاشابة بخلات الزنك المائية تؤثر بشكل ملحوظ على قيم كل من المقادير الكهربائية التالية (C,D, , , ,etc...),وتحسن بشكل واضح في الخصائص العزلية لبوليمير PVA. حيث ازدادتقيم كل من (C,Q, , , )وتناقصت قيم كل من (D, ). بازدياد نسبة الاشابة.